Meeting the needs of the people and the forest: woodfuel and woodland management across the United Kingdom’s Midlands - Rison, J.R.A. (2017)
Building on work in the field of rural geography, this thesis considers the changes which have taken place to the ways in which woods are managed and how the market for woodfuel has evolved following the considerable growth in demand for firewood and woodchip over the past decade. Through the use of in-depth interviews and field visits to woods and woodfuel businesses across the Midlands, it is demonstrated that the growth of the market has encouraged private woodland owners to carry out more management. This is a significant change from the latter half of the 20th Century when falling timber prices, and the lack of a market for wood products generally, resulted in many woodlands being neglected. In particular, the woodfuel markets have stimulated the removal and restoration of ‘Plantation on Ancient Woodland Sites’ (PAWS) by creating a market for the products of first and second thinning operations. Woodland owners are now able to make small, but significant, profits from their woods which is a marked change from a decade ago. A principal driver of the woodfuel market is the ‘Renewable Heat Incentive’ (RHI), whereby the Government is subsidising the use of woodchip-fed biomass boiler systems as part of the transition towards a greater use of renewable energy sources. Whilst the Forestry Commission’s principal objective remains the production of high quality timber, this thesis demonstrates it is reviewing how it may contribute to the woodfuel market’s growing share of the UK’s energy sector. In the thousands of small, privately-owned woods across England, the majority of which are owned for amenity and wildlife purposes, the thesis explores how the growing demand for firewood and woodchip is encouraging greater management. The many ways in which woodfuel management is complementary to other management objectives like timber production, wildlife and shooting are highlighted.